Creativity in the Age of Artificial Intelligence: A Hybrid Human–AI Co-Creation Framework - Maman Sulaeman (UDEX Institute, 2026)
The rapid advancement of generative artificial intelligence (AI) has transformed creative work by shifting creativity from an individual cognitive activity to a hybrid, interactional process involving both human and algorithmic agents. Despite extensive research on creativity and computational systems, existing theories remain fragmented, largely treating human and machine creativity as separate domains and failing to capture their dynamic integration. This study addresses this theoretical gap by reconceptualizing creativity as a distributed, iterative, and hybrid process emerging from human–AI co-creation. Adopting a conceptual and integrative analytical approach, the study synthesizes insights from creativity theory, computational creativity, human–AI interaction, and digital innovation literature to develop a unified theoretical framework. It further introduces a process-oriented Human–AI Creative Co-Creation Model that explains how creative outcomes emerge through stages of intent formation, generative expansion, evaluation, and iterative refinement. The study contributes to theory by redefining creativity as a system-level phenomenon characterized by hybrid agency and co-evolutionary interaction, while offering implications for future empirical research on measuring and managing creativity in AI-mediated environments.